Dataset: Evaluation of pre-driver education interventions using the Theory of Planned Behaviour - Claire Box, Elizabeth (Cranfield University, 2023)
This dataset provides the anonymised data collated for the DriveFit and SDSA Surrey research conducted as part of this PhD thesis research. Participants were informed that anonymised data that underpins the published results would be deposited securely in Cranfield University’s institutional data repository, CORD, which preserves data for at least 10 years after project completion. In addition to the attached datasheet (in SPSS), a word document is also provided, which outlines the survey questions asked as part of this research. Some survey questions have been deleted from the dataset, where they provided more detailed background about ethnicity, or provided open text responses which contained responses that provided irrelevant or incoherent information. The cluster Randomised Controlled Trial (cRCT) evaluation of the DriveFit programme has been published Open Access by Transportation Research Part F: Traffic Psychology and Behaviour: Box, E., Dorn, L. (2023). A cluster randomised controlled trial (cRCT) evaluation of a pre-driver education intervention using the Theory of Planned Behaviour. Transportation Research Part F: Traffic Psychology and Behaviour, 94, p.379-397 https://doi.org/10.1016/j.trf.2023.03.001 For further information about this programme of research, see https://www.racfoundation.org/collaborations/pre-driver-theatre-workshop-education-research-pdtwer
Keywords: Young drivers'; 'Pre-drivers;'; 'Road safety education;'; 'Behaviour Change Techniques (BCTs);'; 'Cluster Randomised Controlled Trial;'; 'Theory of Planned Behaviour;'; 'Implementation intentions;'; 'Process evaluation'